THE EFFECT OF CURRENT RATIO, RETURN ON ASSET, DEBT TO ASSET RATIO, EARNING PER SHARE, AND TOTAL ASSET TURN OVER ON STOCK PRICE IN INFRASTRUCTURE SECTOR COMPANIES LISTED ON THE INDONESIA STOCK EXCHANGE DURING THE PERIOD 2019-2023 - Febdwi Suryani; Desriani Br Karo; Helly Aroza Siregar; Irawati Irawati (Bilancia : Jurnal Ilmiah Akuntansi, 2025)
This Study aims to determine the effect of Current Ratio, Return On Asset, Debt To Asset Ratio, Earning Per Share, Total Asset Tur Over on Stock Prices in the Infrastrukture Sector listed on the Indonesia Stock Exchange for the period 2019-2023. The type of research data used in this study is quantitative data. The data source in this study used secondary data. The sample technique in this study used purposive sampling with the number of samples obtained as many as 52 companies. The research method used is descriptive analysis method and several types of evaluation using SmartPLS software assistance. The results showed that Current Ratio, Total Asset Tur Over has a positive and significant effect on Stock Price.Meanwhile Return On Asset, Debt To Asset Ratio, Earning Per Share have an insignificant negative effect on Stock Price. Penelitian ini bertujuan untuk menganalisis pengaruh Current Ratio, Return on Asset, Debt to Asset Ratio, Earning Per Share, dan Total Asset Turnover terhadap harga saham perusahaan sektor infrastruktur yang terdaftar di Bursa Efek Indonesia periode 2019–2023. Penelitian ini menggunakan pendekatan kuantitatif dengan data sekunder. Teknik pengambilan sampel yang digunakan adalah purposive sampling dengan jumlah sampel sebanyak 52 perusahaan. Metode analisis yang digunakan meliputi analisis statistik deskriptif dan pengujian hipotesis dengan bantuan perangkat lunak SmartPLS. Hasil penelitian menunjukkan bahwa Current Ratio dan Total Asset Turnover berpengaruh positif dan signifikan terhadap harga saham. Sementara itu, Return on Asset, Debt to Asset Ratio, dan Earning Per Share berpengaruh negatif namun tidak signifikan terhadap harga saham.